Pesantren and Politics: Fostering Civil Society-Oriented Political Consciousness in a Muslim Society - Al Humaidy, Mohammad Ali; Afifullah, Afifullah; Harisah, Harisah; Acim, Subhan Abdullah; Ariwidodo, Eko (Universitas Islam Negeri Mataram, 2025)
Political polarization has occurred in Pesantren in the 1999 election, where the kiais involved various political parties. This study aims to examine the politics of the pesantren Annuqayah in Madura and analyze the contribution of it in political democratization and civil society. Although the kiais have different political affiliations, the relationships among kiais, santris, and alumni remain harmonious without open conflict. This phenomenon is crucial to study because it demonstrates the pesantren’s role in fostering healthy and constructive political awareness in society. This article is based on a field study employing a qualitative approach, drawing on the perspectives of social capital and phenomenology. The results show that political democratization in the pesantren is built on respect for the moral authority of kiais, the practice of citizenship values based on the principles of Ahlus Sunnah wal Jama’ah (aswaja), and the strengthening of the tradition of